Connected healthcare for the citizen - Picard, Robert (Health industrialization set., 2018)
Value of Connected Things for Healthcare is based on feedback from members of the LLSA Forum, patients, healthcare professionals, Living Labs, industrialists, researchers and institutional actors confronted with the design, development, implementation and use of these types of tools that penetrate health and communicate data. The term connected object refers to devices that continuously collect data through these objects, providing the state of health of people wherever they are and whatever they do. These objects allow clinical researchers to study new phenomena that have hitherto escaped observations in institutions. However, the mobilization of these technologies in this context poses technical questions because the requirements of a remote, continuous operation are high. What is termed connected health emphasizes the human dimension of the subject, i.e., citizens, patients, health professionals, territorial communities, professional networks, institutions and associations. The questions of who benefits and ethical considerations are paramount to this discussion.